2000
DOI: 10.1002/1521-396x(200009)181:1<77::aid-pssa77>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Tunneling Microscopy and Spectroscopy of Non-Doped, Hydrogen Terminated CVD Diamond

Abstract: The electron emission from a diamond surface is influenced by the surface termination and the surface density of states. It is known that the hydrogen termination of diamond surfaces induces ptype conduction. Scanning tunneling spectroscopy (STS), combined with high-resolution topographical imaging with the scanning tunneling microscope (STM), enables to investigate local variations in the electronic structure of surfaces. We show that the hydrogen termination is sufficient to obtain reproducible STM and STS m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…It was already shown that the surface of hydrogen terminated CVD films shows p-type conductivity [5], but that there can be local differences in the current-voltage (I -V) characteristics [10]. Some groups observe a rectifying behavior [9,14], which we attributed to a Schottky-like contact [9], other groups observe a more symmetrical I -V behavior [11,12]. Both types of curves can be seen on the same films in our previous work, but since the rectifying behavior is statistically observed more frequently, we assume that this is characteristic of the p-type hydrogen terminated CVD films.…”
Section: Introductioncontrasting
confidence: 93%
See 1 more Smart Citation
“…It was already shown that the surface of hydrogen terminated CVD films shows p-type conductivity [5], but that there can be local differences in the current-voltage (I -V) characteristics [10]. Some groups observe a rectifying behavior [9,14], which we attributed to a Schottky-like contact [9], other groups observe a more symmetrical I -V behavior [11,12]. Both types of curves can be seen on the same films in our previous work, but since the rectifying behavior is statistically observed more frequently, we assume that this is characteristic of the p-type hydrogen terminated CVD films.…”
Section: Introductioncontrasting
confidence: 93%
“…3b: much lower current is flowing for the same applied bias. This is in accordance with previous STS results [9,10,23] and measurements examining the change in resistance with temperature [5,8,15,16]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In previous research, microstructures and electrical properties of CVD diamond films that were investigated by atomic force microscopy (AFM) and scanning tunneling microscopy (STM) were studied [6,7]. Current imaging tunneling spectroscopy (CITS) [8] was used to compare the structures and electrical properties of the doped diamond Figure 1(b), the grain size of this film was about 5-20 nm, and the roughness of this film was approximately 1.6 nm.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we applied three scanning probe methods of STM [11], AFM and scanning probe field emission current (SPFEC) measurement [12] to boron-doped and undoped diamonds in order to clarify the relation between the conducting layer and electron emission 100nm 100nm properties. STM and current imaging tunnelling spectroscopy (CITS) were employed for nanoscale characterization [9].…”
Section: Introductionmentioning
confidence: 99%